STUDI PENCEMARAN LIMBAH CAIR DENGAN PARAMETER BOD5 DAN PH DI PASAR IKAN TRADISIONAL DAN PASAR MODERN DI KOTA SEMARANG - Pamungkas, M.T Oktafeni Atur (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Because of its location at the coast, most of the population at Semarang city have a profession as fishermen. Demand for marine products consumption, especially fish have led to a flow of trade between fishermen and buyers. Production process of fish industry requires extensive water thus resulting large amount of wastewater discharged into the surrounding environment. The waste water is contaminating because it contains harmful chemicals, organic and inorganic compounds, either dissolved or suspended and additional compounds that are formed during the production process. Preliminary study of wastewater inspection at the Traditional Fish Market obtained BOD5 level at 1098.25 mg / l. The result exceeds the quality standard established by Central Java Local Regulation Number 5 on 2012, thus further study of fish waste water contamination is needed. The purpose of this study is to determine BOD5 and pH differences at traditional fish market and modern market in Semarang City. The research type is descriptive analytic with purposing sampling method. Sample in this study are waste water from the traditional fish market and modern fish market in Semarang City. Statistical analysis uses Wilcoxon and Mann Whitney test. The result shows there is significant difference between the mean values of BOD5 waste water in the traditional fish market and modern market (p=0,043). There are 10 samples at the traditional market that exceed the BOD5 level of waste water standard quality. For the modern market, there are 6 samples that exceed the BOD5 level of waste water standard quality. The waste water pH level at both market are all still conform the standard quality. Traditional fish market and modern fish market merchants should process the waste water in order not to cause pollution in the surrounding environment.